2011
DOI: 10.1074/jbc.m111.223644
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of the Elicitor Cerato-platanin (CP), the First Member of the CP Fungal Protein Family, Reveals a Double ψβ-Barrel Fold and Carbohydrate Binding

Abstract: Cerato-platanin (CP) is a secretion protein produced by the fungal pathogen Ceratocystis platani, the causal agent of the plane canker disease and the first member of the CP family. CP is considered a pathogen-associated molecular pattern because it induces various defense responses in the host, including production of phytoalexins and cell death. Although much is known about the properties of CP and related proteins as elicitors of plant defense mechanisms, its biochemical activity and host target(s) remain e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
92
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 100 publications
(97 citation statements)
references
References 67 publications
5
92
0
Order By: Relevance
“…As expected on the basis of previously obtained results with CP on carboxymethylcellulose (de Oliveira et al 2011), during the action of CP and Pop1 on filter paper, no detectable amount of reducing sugars was produced (data not shown). It has recently been shown that glycosyl hydrolases GH61 can internally cleave cellulose molecules in a direct oxidative way that does not lead to the generation of new reducing ends (Westereng et al 2011).…”
Section: Resultssupporting
confidence: 69%
See 3 more Smart Citations
“…As expected on the basis of previously obtained results with CP on carboxymethylcellulose (de Oliveira et al 2011), during the action of CP and Pop1 on filter paper, no detectable amount of reducing sugars was produced (data not shown). It has recently been shown that glycosyl hydrolases GH61 can internally cleave cellulose molecules in a direct oxidative way that does not lead to the generation of new reducing ends (Westereng et al 2011).…”
Section: Resultssupporting
confidence: 69%
“…CP, like the orthologous protein Pop1, weakened filter paper in a concentration-dependent manner. No detectable amount of reducing sugars was released by CP and Pop1 during the action on filter paper, thus confirming a lack of β-1,4-glucanase activity that had already been reported for CP on carboxymethylcellulose (de Oliveira et al 2011). At the same time, we also excluded the possibility that the weakening activity was the result of an oxidative mechanism like that recently found for the glycosyl hydrolases GH61 that does not lead to the generation of new reducing ends (Westereng et al 2011;Žifčáková and Baldrian 2012).…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…However, hydropathy plots of cerato-platanin proteins show that they have fewer hydrophobic regions than hydrophobins, suggesting that these proteins have at least slightly different properties from "traditional" hydrophobins (14). Recently, an NMR-based structural study of CP showed that this protein has structural features that are similar to Barwin-like endoglucanases and plant expansins, which are involved in plant cell wall extension (19). Furthermore, based on structural NMR data, an N-acetylglucosamine binding pocket was found in CP; this is interesting in view of the fact that chitin, which is composed of N-acetylglucosamine monomers, is a structural component of the fungal cell wall.…”
mentioning
confidence: 99%